The relationship between environmental factors and health problems of secondary school students in Oyo State, Nigeria (2008)
This study investigated the relationship between Environmental factors and health problems of students in Oyo state Nigeria. The environment in which a child stays and learns as a direct effect on his/her health status. The classroom environment where too many students sit together to learn is likely to predispose them to infections and other health related problems. The number of students in a classroom can affect tire condition of the environment where proper ventilation is not possible and the spread of diseases become more prominent. The condition will therefore put the health of those students in jeopardy. A sample of 2000 respondents was used for the study. Data collection involved the use of questionnaire while data analysis was done using frequency counts and percentages. The findings revealed that faulty refuse disposal, lack of toilet facilities, crowded classrooms and poor water supply as environmental factors predisposed the students to health problems. These findings have implications for curriculum planners and policy makers who are interested in the well being of the child.